PENGARUH PENGGUNAAN MODEL KOOPERATIF TIPE STAD TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 12 TANJUNG JABUNG TIMUR - Andi Santoso; Abdoel Gafar; Firman Tara (Universitas Batanghari, 2020)
This purposes of this research are (1) to identify the effect of the cooperative model STAD type on students’ writing skill of seventh grade students of SMP Negeri 12 Tanjung Jabung Timur academic year 2019/2020, and (2) to describe the steps of writing descriptive text through the cooperative model STAD type of class VII students of SMP Negeri 12 Tanjung Jabung Timur academic year 2019/2020. This research is Quasi-Experimental. The subjects of the research was the students of class VII SMP Negeri 12 Tanjung Jabung Timur in which 30 students in control class and 30 students in experimental class. The data was taken by written test techniques. The data analysis was done by calculating the total score of the control class and the experimental class of each student which was then compared with their skill categories. The indicator of success in this research is the effect of students’ ability in writing descriptive text in class VII of SMP Negeri 12 Tanjung Jabung Timur through the use of cooperative learning model STAD type. This research is said to be successful if the percentage of the students in the experimental class is 82.63 higher than the control class which falls into 70.20. The results showed: (1) the use of cooperative learning model type STAD has an effect in writing descriptive text. (2) The steps of the cooperative learning model STAD type in writing descriptive text are: 1) conveying goals and motivating students, 2) presenting information, 3) organizing students in cooperative groups, 4) guiding groups to work and study, 5) evaluating, and 6) giving awards. Thus the cooperative learning model STAD type significantly influence students’ skill in writing descriptive text.